A mesocosm comparison of laboratory‐based and on‐site eDNA solutions for detection and quantification of striped bass (Morone saxatilis) in marine ecosystems. Issue 3 (8th January 2020) - Skinner, Marc; Murdoch, Mary; Loeza‐Quintana, Tzitziki; Crookes, Steve; Hanner, Robert
Abstract: Environmental effects monitoring in marine ecosystems are challenging, particularly in dynamic macrotidal settings like the Bay of Fundy. Environmental DNA provides a useful tool for determining species presence in such challenging places to access and sample. Moreover, recent studies showing a link between eDNA concentration and fish density/biomass reveal the great promise for eDNA tools to improve biodiversity assessments in marine environments. Three mesocosm experiments were conducted to assess the accuracy and precision of a handheld point‐of‐need (PoN) tool for quantitative polymerase chain reaction (qPCR) assay for eDNA detection of striped bass ( Morone saxatilis ) versus conventional laboratory‐based eDNA techniques. The first of these experiments determined that striped bass eDNA was reliably detected using either of the laboratory‐based or PoN platforms, with some variation observed in the estimates of eDNA concentrations derived from each. Next, a time series experiment established that eDNA in water samples collected within a 24‐hrs period of exposure to striped bass was reliably and consistently detectable with either platform. Our final experiment found that the relationship between eDNA concentrations and manipulated striped bass stocking densities was significant and positive based on results from each of the laboratory‐based or PoN platforms. Our results validate and advance eDNA approaches toward environmental monitoring efforts and demonstrate the potential for real‐time eDNA tools to quantify and identify the spatial and temporal distribution of species‐at‐risk in an open ocean environment. Abstract : Environmental monitoring in marine ecosystems is challenging, and eDNA provides a useful tool for determining species presence in such places. Our results validate and advance eDNA approaches toward environmental monitoring efforts and demonstrate the potential for eDNA tools to quantify and identify the spatial and temporal distribution of species‐at‐risk in an open ocean environment.